Emphysematous cholecystitis in a patient with porcelain gallbladder. Issue 1 (17th January 2023) - Vera, Vithya; Sharma, Abhimanyu; Townson, Adam T; Azeem, Qasim; Malam, Yogeshkumar; Mathews, John
Abstract: Our case uniquely presents a patient with two rare gallbladder disease entities occurring simultaneously. The patient presented to hospital with abdominal pain and was subsequently diagnosed with emphysematous cholecystitis and porcelain gallbladder. After initial conservative management failed, cholecystectomy was performed, and the patient recovered well post-operatively and was discharged home.